2020
DOI: 10.1634/theoncologist.2020-0165
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-DOTATATE Positron Emission Tomography-Computed Tomography Quantification Predicts Response to Somatostatin Analog Therapy in Gastroenteropancreatic Neuroendocrine Tumors

Abstract: Background. Somatostatin analogs (SSAs) are the frontline antitumor therapy in advanced well-differentiated gastroenteropancreatic neuroendocrine tumors (GEP-NETs). A subset of patients demonstrate early disease progression on SSA therapy, yet the currently known predictors for treatment failure lack specificity to affect therapeutic decision. SSAs target tumor somatostatin receptors, the level of which can be quantitatively assessed with 68 Ga-DOTATATE positron emission tomography-computed tomography (PET/CT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…The [ 68 Ga]Ga-DOTA-FAPI-04 uptake is much lower when compared to PDAC, implying the low expression of FAP. [ 68 Ga]Ga-DOTA-TATE has an established role in diagnosing NENs [27,28]. In our study, one patient with NET (G2) also conducted [ 68 Ga]Ga-DOTA-TATE PET/CT and the corresponding liver metastases (FAPI − /FDG − ) showed intense uptake.…”
Section: Clinical Characteristics Of the Patientsmentioning
confidence: 72%
“…The [ 68 Ga]Ga-DOTA-FAPI-04 uptake is much lower when compared to PDAC, implying the low expression of FAP. [ 68 Ga]Ga-DOTA-TATE has an established role in diagnosing NENs [27,28]. In our study, one patient with NET (G2) also conducted [ 68 Ga]Ga-DOTA-TATE PET/CT and the corresponding liver metastases (FAPI − /FDG − ) showed intense uptake.…”
Section: Clinical Characteristics Of the Patientsmentioning
confidence: 72%
“…There is a clear relation between SUV uptake (minimum, maximum, and mean) with the selection of patients for PRRT, which can explain differences in response and should be used to select patients for PRRT. Previous studies showed that low SUVmax on 68Ga-DOTATATOC PET-CT independently predicts early failure on somatostatin receptor analog monotherapy in patients with well-differentiated grade 1 -2 NET [24].…”
Section: Discussionmentioning
confidence: 99%
“…Pauwels et al 18 The same as for volumetric parameters, only few studies focused on SUVmax as a predictive parameter in GEP-NET. 13,23 Low SUVmax on [ 68 Ga]Ga-SSTR PET was associated with worse prognosis in well-differentiated GEP-NET predicting early failure on SSA monotherapy. In addition, [ 68 Ga]Ga-SSTR PET/CT, via SUVmax, impacted on the management of NET patients, leading to a change in treatment decision in about one-third of patients.…”
Section: Discussionmentioning
confidence: 99%